(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
The thermal properties of textiles are essential for ensuring the comfort of both fabric and clothing systems. Phase change materials (PCMs), which contain latent heat, play a significant role in this area. As ambient temperature fluctuates, PCMs absorb heat, melt or release heat, and solidify. Throughout these melting and crystallizing processes, the temperature of the PCM remains constant. Integrating suitable PCMs into garments helps maintain a stable temperature within the micro-environment between the garment and the wearer. The effectiveness depends on the quantity of PCMs used. This study synthesised and evaluated a novel type of nano-capsule containing PCM Glauber’s salt. Advanced techniques such as Differential Scanning Calorimetry (DSC), Scanning Electron Microscopy (SEM), and Fourier-Transform Infrared Spectroscopy (FTIR) were employed to analyze the developed nano-capsules. Additionally, a finite element model was created to enhance the understanding of the thermal mechanisms in textiles incorporating PCMs. This comprehensive analysis aims to promote the application of PCMs in protective textiles, contributing to developing next-generation materials that provide thermal regulation and protection for the wearer.